Research on the Coal Seam Permeability-Increasing Technology via High-Pressure Water Jet Reaming and Its Application. (4th March 2021) - Niu, Xingang; Shi, Biming; Zhang, Zhigang; Zhang, Yongjiang
Abstract : Aiming at the problem of coal and gas outburst prevention and control in serious outburst dangerous coal seam under complex geological conditions in Qidong Coal Mine, the water jet drilling and expanding integrated device was used to implement the measures that expand holes and increase permeability by high-pressure water at a 912 working face. The experimental results show that when the pump pressure is between 13 MPa and 15 MPa, the particle size of pulverized coal can be effectively reduced and the discharge of pulverized coal can be increased. The coal output of a single hole is 0.8 2.3 t/m, with an average of 1.1 m/t. The unreamed conventional borehole has a single-hole initial gas drainage rate of 50.74 m 3 /d and a single-hole cumulative gas drainage rate of 736.12 m 3 within 30 days. The initial single-hole gas drainage volume of the reaming borehole is 178.74 m 3 /d, and the cumulative single-hole gas drainage volume in 30 days is 2227.57 m 3 . After reaming, the initial gas drainage scalar of a single hole increases 3.52 times of the original unreamed conventional drilling and the average cumulative gas drainage scalar of a single hole reaches 3.03 times of the original unreamed conventional drilling. This technology and equipment have a good promotion and application value in gas treatment of soft, low-permeable coal seams.